The application of DNA fingerprinting to the conservation of threatened species - Ashworth, David (1992)
The human polycore minisatellite probes 33.6 and 33.15 developed by Prof. Alec Jeffreys and colleagues have been shown to detect hypervariable minisatellites in many taxonomically dispersed species. The mRNA derivatives of these two probes, pSPT19.6 and pSPT18.15, have here been used to probe the genomes of four species currently maintained in captivity. The wild populations of these species, Rothschild's mynah, the Rodrigues fruit bat, the British Merlin and the New Zealand falcon, are threatened with extinction to varying degrees. By using the technique of DNA fingerprinting, it has been possible to assess the levels of minisatellite variation remaining in these stocks, to confirm or refute the parent/offspring allocations made within, and in the case of Rothschild's mynah, to demonstrate that at least two of the founders of the stock were closely related. In addition, it has been possible to show that there is a significant positive relationship between the similarity coefficient calculated between two adults and the inbreeding coefficient calculated for their offspring.